PERFORMANCE AND FORECAST OF INDONESIAN RUBBER EXPORTS TO THE CENTRAL EUROPEAN COUNTRIES - Agus Dwi Nugroho; Imade Yoga Prasada; Zoltan Lakner (OISAA, 2022)
The price and consumption of rubber experienced a decline due to the global economic crisis, the US-China trade war, and coronavirus. This situation is unprofitable for Indonesia, and it must develop new target markets. Central Europe is one of the potential markets for Indonesian rubber. This study aims to ascertain the performance of the Indonesian rubber exports to Central European countries and forecast its future. The research used Indonesian rubber export data to Hungary, Poland, and Romania from January 1999 to March 2021. Descriptive statistics and autoregressive integrated moving averages were used to analyze the data. In the last three decades, Indonesian rubber exports to Central Europe have risen. The short-term forecasting indicates that Indonesian rubber exports to Poland will increase; on the other hand, exports to Romania will experience a decline. Meanwhile, exports to Hungary were relatively stable. This result was obtained using ARIMA estimation with different models for each country, respectively ARIMA(1,0,5) in Poland, ARIMA(2,0,1) in Romania, and ARIMA(2,0,1) in Hungary.